PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, STRES KERJA DAN KOMPETENSI GURU TERHADAP KINERJA GURU - Melly, Melly (Jurnal Ilmu Manajemen, 2017)
This study aimed to determine the effect of school leadership, the stress ofwork and competence of teachers on teacher performance SMK inBanyuasin. So the problem is formulated in this study is there any influenceof school leadership, the stress of work and competence of teachers onteacher performance SMK in Banyuasin.The data used in this study are primary data from respondents as many as145 people Teachers SMK in Banyuasin. The analytical method used ismultiple linear regression and by testing the validity and reliability of data.Test data used to determine the characteristics of the data that is test ofnormality and linearity test. Test models used consists of multicollinearitytest and test heterokedastisitas, aided analysis tools SPSS for WindowsVersion 20.0 with a significant level of ? = 0.05.The results of multiple linear regression showed principal leadership, workstress, and teacher competence jointly have a significant influence on theperformance of teachers. Partially school leadership but very little effect onthe performance of teachers, job stress negatively affect the performanceand competence of teachers' positive and significant impact on teacherperformance.